Analisis Persepsi Masyarakat Mengenai Pilkada Serentak Tahun 2020 Pada Masa Pandemi Covid19 Rt 11 Kelurahan Tungkal II Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat: Analisis persepsi pilkada serentak - Deskalia, Chindy; Anderson, Irzal; Dona Sariani (Citizenship Education, Faculty of Education, Jambi University, 2022)
The election of regional heads is one part of the democratic mechanism and is the main gate in building leadership in the regions. The community of Rt 11 Tungkal II Village, Tungkal Ilir District, Tanjung Jabung Barat Regency has successfully carried out the simultaneous elections on December 9, 2020, there are 2 perceptions put forward by the community, namely positive perceptions and negative perceptions. The negative perception conveyed was that the simultaneous regional elections in 2020 were like a political conspiracy where if other people did not use their voting rights or abstentions would be misused or fraud would occur, and the campaign delivered during this pandemic was indirect so that many people did not know the vision and mission. candidates, and there are some people who vote forcibly because of political money or dawn attacks. This research uses qualitative research methods. This study aims to determine the perception of the people of Rt 11 Tungkal II Village, Tungkal Ilir District, Tanjung Jabung Barat Regency in the simultaneous regional head election in 2020, in this study the public perception expressed is different, some have a positive perception and some have a negative perception. The perception conveyed by the informant is in accordance with the experience or circumstances obtained. From these different perceptions, different opinions emerge from each informant, the positive perception conveyed by the community is more directed towards the candidate pair of candidates such as the vision-mission, work program and personality of the candidate, while the negative perception conveyed by the public is more of an attack on dawn or political money and campaign rules in the 2020 simultaneous elections. Keywords : Public Perception, simultaneous elections